Relationship between residual feed intake and digestive traits of fattening bulls fed grass silage- or maize silage-based diets - M. Coppa; C. Martin; A. Bes; L. Ragionieri; F. Ravanetti; P. Lund; G. Cantalapiedra-Hijar; P. Nozière (Animal, 2023)
Several studies tried to identify digestive determinants of individual variation in feed efficiency between fattening bulls, because of their importance for breeding and management strategies. Most studies focused on single traits or single diet. Little is known about diet-dependent differences in digestive determinants and on their relative importance in distinguishing divergent residual feed intake (RFI) bulls. This research aimed (i) to identify digestive traits that differed between bulls diverging in RFI and fed a maize silage- or a grass silage-based diets; (ii) to highlight the relationships between RFI and digestive traits, and (iii) to explore the hierarchy among digestive traits in discriminating RFI divergent bulls. After an initial RFI test of 84 days on 100 Charolais growing bulls fed two different diets based on grass silage (GS), or maize silage (MS), the 32 most RFI divergent bulls were selected (eight efficient RFI− and eight inefficient RFI+ bulls per diet) and measured thereafter for total tract apparent digestibility and transit rate, enteric gas emissions (CH4 and H2), rumen pH, and feeding behaviour. Rumen particle size and visceral organ and reticulo-omasal orifice (ROO) sizes and rumen and ileum histology were measured at slaughter on the 32 selected extreme RFI bulls. Irrespective of the diet, efficient bulls (RFI−) had lower rumen size, CH4 yield (g/kg DM intake; tendency), lower number of cells in the ileal crypts, tended to have longer time of rumen pH below 5.8 and lower proportion of small size particles in rumen content than non-efficient bulls (RFI+). A long-term test for feed efficiency (197 d on average) was performed on the whole experimental period until slaughter for the 100 animals. The long-term RFI value was negatively related to time spent in activity other than ingestion, rumination, and resting, and positively related (tendency) to the duration of ingestion events, to rumen and abomasum size, irrespective of the diet. Diet-dependent effects were noted: with GS, efficient (RFI−) bulls showed a slower transit rate, whereas with MS, efficient (RFI−) bulls tended to have shorter resting events and a smaller ROO than inefficient bulls (RFI+). The transit rate and the ROO size tended to be positively related, while total tract apparent digestibility of nitrogen was negatively related to long-term RFI value, but only in GS. Rumen size appeared as the most discriminating digestive variable between RFI divergent bulls, but this result should be validated on a larger number of animals and diets.